2017
DOI: 10.1590/1089-6891v18e-34828
|View full text |Cite
|
Sign up to set email alerts
|

Histomorfometria De Orgãos Linfoides E Desenvolvimento Intestinal De Pintos De Corte Originados De Matrizes Com Diferentes Idades E Submetidos Ao Estresse Por Calor Na Incubação

Abstract: Resumo: Objetivou-se avaliar o efeito da idade da matriz e da variação da temperatura de incubação sobre a qualidade do pinto neonato. O delineamento foi inteiramente casualizado em esquema fatorial 3x2 (três idades x duas temperaturas de incubação). Foram incubados 720 ovos, provenientes de matrizes com diferentes idades (30, 42 ou 64 semanas). A temperatura da máquina de incubar para os grupos controle foi mantida constante (37,5 ºC) e para os tratamentos com estresse por calor foi aplicada uma temperatura d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Moreover, studies showed that EST can also affect development of primary immune organs. For instance, histology of the bursa, gastrointestinal tract, spleen, and thymus at hatch were affected by high (38.1°C–39.0°C) incubator temperatures ( Oznurlu et al., 2010 ; Liu et al., 2013 ; Leandro et al., 2017 ). Therefore, adjustments in EST patterns can potentially improve embryo immune organ development.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies showed that EST can also affect development of primary immune organs. For instance, histology of the bursa, gastrointestinal tract, spleen, and thymus at hatch were affected by high (38.1°C–39.0°C) incubator temperatures ( Oznurlu et al., 2010 ; Liu et al., 2013 ; Leandro et al., 2017 ). Therefore, adjustments in EST patterns can potentially improve embryo immune organ development.…”
Section: Introductionmentioning
confidence: 99%
“…Broilers born to older breeders showed a higher lymphocyte count in the bursa at 21 days of age. Leandro et al (2017) reported that chicks from older breeders exhibited greater immune response than chicks from young breeders, whereas birds from older breeders showed a larger follicular area in the bursa. At seven days of age, valine supplementation above 11.2 and 10.2 g/kg increased the lymphocyte count in the spleen and bursa, respectively, whereas the lymphocyte count in the thymus was not influenced by valine supplementation above 10.2 g/kg in the thymus of older breeders (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…O processo de depleção linfocitária é mediado por intensificação da morte celular programada, também conhecida como apoptose, principalmente na bolsa cloacal, tanto que este órgão é frequentemente adotado para avaliar a resposta em casos de estresse (Revidatti et al, 2002;Leandro et al, 2017;Sobhi et al, 2020;Wang et al, 2023).…”
Section: Variáveisunclassified